Legal Profession and Corruption in Health Care: Some Reflective Realities in South Africa - Evangelos Mantzaris; Pregala Pillay (Frontiers Media S.A., 2021)
The article is an empirical attempt to research, analyse, and dissect the corrupt involvement of legal practitioners in illegal and fraudulent acts, and mainly their involvement in litigation associated with issues of medical negligence. This is done primarily but not exclusively through the utilisation of several qualitative research methods, including the content analysis of primary literary sources such as official state documents, existing legislation and court proceedings and personal interviews with senior public servants, as well as secondary sources. Beginning with a short exploration of South Africa's public legal terrain and the fears of sections of the statutory leadership of the legal profession, the article continues with the identification of key findings in several the country's provinces, the modus operandi of the corrupt individuals and groups, as well as the monetary, financial and social repercussions of such actions.